Analisis Strategi Komunikasi Pemasaran dalam Meningkatkan Loyalitas Pelanggan di BPR Kusuma Sumbing Delanggu - Nur Sahid Gatot nugroho; R.Taufiq Nur Multiyanto; Indra Hastuti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
BPR in Indonesia. This study uses qualitative research methodology. The methodology employed is a case study. The findings of this investigation include (1) Marketing communication strategies in increasing customer loyalty at BPR Kusuma Sumbing Delanggu are by using 1) advertising, BPR Kusuma Sumbing Delanggu utilizes digital media, only using Facebook, Instagram and the BPR Kusuma Sumbing Delanggu website. 2) sales promotion, promotions using distributing brochures, installing banners, personal and non-personal sales by visiting customers directly. 3) Public relations, BPR Kusuma Sumbing Delanggu is building a positive image of the company through events, sponsorships, or CSR. 4) digital media promotion, digital media used in marketing BPR Kusuma Sumbing Delanggu uses social media such as Instagram and Facebook, and we also have a special website for BPR Kusuma Sumbing Delanggu with the website address. (2) BPR Kusuma Sumbing's challenge is that educational communication regarding BPR Kusuma Sumbing Delanggu products to customers is sometimes hampered by a lack of understanding of financial literacy. Therefore, I have to explain in detail and coherently, which takes quite a long time. (3) The solution to addressing the challenges in marketing communication strategies to increase customer loyalty at BPR Kusuma Sumbing Delanggu is to continuously improve customer relationships and expand our reach. By strengthening communication and providing better education, we believe we can increase customer loyalty and the BPR's future growth.